Biomechanical comparisons of knee stability after anterior cruciate ligament reconstruction between 2 clinically available transtibial procedures anatomic double bundle versus single bundle - Kondo, E.; Merican, A.M.; Yasuda, K.; Amis, A.A. (SAGE Publications (UK and US), 2010)
Background: Several trials have compared the clinical results between anatomic double-bundle and single-bundle anterior cruciate ligament reconstruction procedures. However, it remains controversial whether the anatomic double-bundle procedure is superior to the single-bundle procedure. Hypothesis: The anatomic double-bundle procedure will be better than the single-bundle procedure at resisting anterior laxity, internal rotation laxity, and pivot-shift instability. Study Design: Controlled laboratory study. Methods: Eight cadaveric knees were tested in a 6 degrees of freedom rig using the following loading conditions: 90-N anterior tibial force, 5-N.m internal and external tibial torques, and a simulated pivot-shift test. Tibiofemoral kinematics during the flexion-extension cycle were recorded with an optical tracking system for (1) intact, (2) anterior cruciate ligament deficient knee, (3) anatomic double-bundle reconstruction, and (4) single-bundle reconstruction placed at 11 o'clock in the intercondylar notch. Results: There were significant reductions of anterior laxity of 3.5 mm at 20 degrees of flexion, internal rotational laxity of 2.5 degrees at 20 degrees of flexion, and anterior translations (2 mm) and internal rotations (5 degrees) in the simulated pivot-shift test in the double-bundle reconstruction compared with the single-bundle reconstruction. There were no significant differences between the 2 procedures for external rotation laxity. Conclusion: The postoperative anterior translation and internal rotation stability after anatomic double-bundle anterior cruciate ligament reconstruction were significantly better than after single-bundle reconstruction, in both static tests and the pivot shift. \textbackslashClinical Relevance: Unlike previous laboratory studies, this work used clinical arthroscopic methods for anterior cruciate ligament reconstruction, and found that the anatomic reconstruction was superior to a single graft placed at 11 o'clock.